A new intermediate between active cathode materials and precursors

JP2024522006A5Inactive Publication Date: 2025-02-18NANO ONE MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023571431
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-05-17
Filing Date
2022-05-16
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for forming active cathode materials in lithium ion batteries rely heavily on high-temperature furnaces and ceramic kiln tools, which are costly, inefficient, and require frequent replacement due to corrosion from molten lithium hydroxide, limiting production volume and efficiency.

Method used

A method involving the formation of an intermediate material from a precursor in a metal-lined container at lower temperatures (below 600°C) followed by further heating to form the active cathode material, using metal-lined rotary kilns or stirring to create a free-flowing powder, reducing reliance on high-temperature furnaces and ceramic tools.

Benefits of technology

This approach significantly reduces costs, increases manufacturing efficiency, and extends the life of kiln tools by eliminating the need for frequent replacements, while enabling large-scale production of high-purity active cathode materials with controlled oxygen partial pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Methods for forming active cathode materials. The method includes forming a precursor including a lithium salt and at least one multicarboxylate of nickel, manganese, or cobalt, heating the precursor to a temperature up to 600° C. in a metal-lined vessel to form an intermediate material, and heating the intermediate material to a temperature above 600° C. to form the active cathode material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS REFERENCE TO RELATED APPLICATIONS: This application claims priority to pending U.S. Provisional Patent Application No. 63 / 189,334, filed May 17, 2021, the contents of which are incorporated herein by reference.

[0002] TECHNICAL FIELD OF THEINVENTION The present invention relates to the formation of an intermediate material that is formed after formation of a cathode material precursor and prior to calcination to form an active cathode material. More specifically, the present invention relates to a novel material that can be formed in large quantities in a metal-lined, preferably rotary, kiln, thereby reducing dependency on high temperature kilns and the ceramic kiln furniture used therein. [Background technology]

[0003] A recently developed process for forming active cathode materials is referred to in the art as the one-pot process. This method is particularly suited to the formation of cathode materials containing oxides of lithium, nickel, manganese, and optionally cobalt, in a crystal lattice, particularly a spinel lattice, referred to in the art as NMC. The one-pot method involves the initial formation of an organic salt of lithium and the metal, referred to herein as the precursor, which is heated to a calcination temperature to form the lithium metal oxide that functions as the cathode in the battery.

[0004] Specific examples of precursor organic salts include, but are not limited to, multicarboxylates, and oxalates are exemplified. The formation of such active cathode materials utilizing precursors is described in commonly owned U.S. Patent Publications; U.S. Patent Application No. 2019 / 0372120 published on December 5, 2019; U.S. Patent Application No. 2020 / 0373560, published on November 26, 2020; and Patent Application No. 2021 / 00028448 published on January 28, 2021. These are incorporated herein by reference in their entireties.

[0005] During calcination, the precursor loses 50-66% of its mass by weight, the losses being primarily CO2 and water, which displace the kiln atmosphere that controls the oxygen partial pressure throughout the bulk of the powder, making it difficult to control.

[0006] Regardless of origin, yet another problem associated with precursors is the reliance on high temperature furnaces and kiln furniture for use within the furnace. Kiln furniture such as saggers and the like are typically manufactured from ceramic materials that must be replaced frequently. Ceramic is necessary because the typical process for cathode manufacture involves using lithium hydroxide as a lithium source. The lithium hydroxide melts early in the heating process, and molten lithium hydroxide is extremely corrosive. Molten lithium hydroxide also precludes the opportunity to use any type of rotary kiln, as the molten lithium hydroxide will coat and deteriorate the kiln surfaces. Thus, the process is limited to a relatively low volume, stagnant heating process using ceramic saggers.

[0007] The present invention provides for the formation of an intermediate material formed between a precursor and a calcined oxide, where the intermediate material is formed in bulk, in contact with a metal, and isolated or transferred directly to a kiln for calcination. The present invention eliminates many of the problems associated with calcining precursors to form active cathodes for use in lithium ion batteries. Summary of the Invention

[0008] The present invention relates to an improved method for forming lithium ion cathode materials, particularly lithium ion cathode materials comprising lithium metal oxides containing nickel, manganese and optionally cobalt.

[0009] A feature of the present invention relates particularly to the ability to form intermediate materials from precursors, which can be formed while in contact with metals, thereby significantly reducing costs and increasing manufacturing efficiency.

[0010] Another particular feature is the ability to form the intermediate material in bulk from the precursors by tumbling or stirring, resulting in a fine powder that can be isolated or passed directly into a kiln for further heating to mineralization.

[0011] A particular advantage of the present invention is the ability to form calcined cathode material from an intermediate material that is already lithiated, reducing the volume of material added to the kiln and the time required to calcify the intermediate material, thereby reducing the time at calcination temperatures, increasing manufacturing efficiency, and improving capital cost per volume of calcined material produced.

[0012] Yet another particular advantage is the elimination of liquid lithium hydroxide, which increases the useful life of the kiln equipment.

[0013] These and other advantages may be realized in a process for forming an active cathode material that includes: forming a precursor comprising a lithium salt and at least one multicarboxylate of nickel, manganese or cobalt; heating the precursor in a metal-lined vessel to a temperature of 600° C. or less to form an intermediate material; and heating the intermediate material to a temperature of 600° C. or greater to form the active cathode material.

[0014] Yet another embodiment is provided in a process for forming an active cathode material comprising: forming a precursor comprising a lithium salt and at least one multicarboxylate of nickel, manganese or cobalt; heating the precursor in a first vessel to a temperature of 600° C. or less to form an intermediate material; transferring the intermediate material to a second container; and and heating the intermediate material in the second container to a temperature greater than 600° C. to form the active cathode material.

[0015] Yet another embodiment is a method of forming an active cathode material comprising: forming a precursor comprising lithium oxalate and at least one multicarboxylate of nickel, manganese or cobalt; heating the precursor to a temperature of 600° C. or less in a rotary kiln vessel to form an intermediate material; and heating the intermediate material to a temperature greater than 600° C. to form the active cathode material.

[0016] Yet another embodiment is provided in an intermediate material to an active cathode material having a formula selected from the group consisting of: LiNi x Mn y Co z E w O4 Formula I where E is an optional dopant; and x+y+z+w = 2 and w≦0.2 and LiNi a Mn b X c G d O2 formula II where G is an optional dopant; X is Co or Al; and Wherein a+b+c+d=1 and d≦0.1; and The intermediate material is at least 7m 2 / g surface area. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a graphical representation illustrating the advantages of the present invention.

[0018] [Diagram 2] FIG. 2 is a graphical representation illustrating the advantages of the present invention.

[0019] [Diagram 3] FIG. 3 is a graphical representation illustrating the advantages of the present invention.

[0020] [Figure 4] FIG. 4 is a flow chart representation of an embodiment of the present invention. Modes for carrying out the invention

[0021] The present invention relates to an improved method for forming an active cathode material and to the formation of an intermediate material which can be formed in contact with a metal. More specifically, the present invention relates to a method for forming an intermediate material into an active cathode material, which can be formed in high volume in contact with a metal at lower temperatures, and the precursor can be subjected to a rotating action or stirring during heating to form the intermediate material.

[0022] Precursors to active cathode materials formed utilizing multi-carboxylates such as oxalic acid evolve CO2 and water during heating. Surprisingly, it has been discovered that pre-calcining the precursor in air or oxygen at temperatures between 200°C and 600°C decomposes organic salts such as, but not limited to, oxalates to preferred lithiated mixed metal oxides. Particular advantages are realized by incorporating lithium organic salts, such as, but not limited to, lithium oxalate, where the lithium organic salt forms lithium oxide directly without forming a liquid phase. The combination of lower temperatures and removal of the lithium-containing liquid phase allows for an initial heating step at or below about 600°C to be carried out in the presence of metal, which heating can be carried out with rotation or stirring, thereby resulting in an intermediate material that is a free-flowing powder. Particularly preferred lithium salts include mono- and multi-carboxylates, with lithium acetate and lithium oxalate being exemplary.

[0023] After formation of the intermediate material, below about 600° C., the intermediate material powder can be calcined in a more controlled atmosphere to a temperature of 700° C. to 925° C. to form the final active cathode material. A particular advantage provided by the present invention is that the intermediate material has a stoichiometry close to that of the final cathode material. During the second calcination to form the active cathode material from the intermediate material, the release of volatile components is minimal, which optimizes kiln utilization.

[0024] The intermediate material has less than 10 wt% carbon, more preferably 9 wt% or less carbon, more preferably 8 wt% or less carbon, more preferably 7 wt% or less carbon, more preferably 6 wt% or less carbon, more preferably 5 wt% or less carbon. More preferably, the intermediate material has 4.5 wt% or less carbon, even more preferably 4 wt% or less carbon, even more preferably 3 wt% or less carbon, even more preferably 2 wt% or less carbon, even more preferably 1 wt% or less carbon, even more preferably 0.5 wt% or less carbon, even more preferably 0.4 wt% or less carbon, and most preferably no detectable carbon, as determined by ASTM E1019-11.

[0025] The invention will now be described with reference to the drawings which constitute a necessary but non-limiting component of the disclosure of the invention.

[0026] An embodiment of the present invention will now be described with reference to Figure 4, which is shown in a flow chart representation. In Figure 4, a precursor is formed at 10 (Figure 4), the precursor comprising salts of metals and multi-carboxylic acids, the metals comprising nickel, manganese, and optionally cobalt. The precursor also comprises a lithium multi-carboxylic acid salt or lithium carbonate, with lithium oxalate being preferred.

[0027] The precursor is heated in the first vessel to 12°C to 600°C or less, where the precursor is preferably in contact with a metal during heating. In one embodiment, the surface of the first vessel that contacts the precursor is made of or formed from a metal. The metal is not particularly limited herein, and any metal currently utilized to form kiln linings or metal saggers is suitable for demonstration of the present invention. Particularly suitable for demonstration of the present invention are nickel-based alloys such as Inconel® alloys, including, but not limited to, Inconel® 601, Inconel® HX, and Inconel® MA 956. In a particularly preferred environment, the vessel is a metal-lined (also called lined) furnace, with metal-lined rotary furnaces being particularly preferred. Without being limited to theory, it is hypothesized that rotation or stirring of the precursor during calcination improves the reaction because CO2 and water evolution from the inner portions of the powder is more efficient and the formation of a kinetically favorable crystal lattice (which is ultimately the same as the active cathode material) can be more easily formed since powder movement minimizes the need for metal movement to achieve the desired crystal lattice. After heating the precursor in the first vessel for a sufficient time, an intermediate material is obtained.

[0028] The intermediate material is optionally, but preferably, transferred to a second vessel for subsequent heating at 14 (FIG. 4). Metal-lined vessels are less desirable for heating the intermediate material to the extent necessary to form the active cathode components. The intermediate material is heated to a preferred temperature of about 700° C. to 925° C. for a sufficient time to form the active cathode material at 16 (FIG. 4). Without being limited by theory, it is hypothesized that the use of some form of agitation during the initial heating in the first vessel causes the lithium and metal to form the desired crystal structure for the active cathode material, and thus the second heating in the second vessel serves to increase the size of the crystals. Since the crystals are already lithiated in the first heating in the first vessel, the prior art method of heating for a sufficient time for the lithium to migrate into the lattice is not necessary. After the second heating, in the second vessel, the active cathode material is obtained at 18 (FIG. 4) and the cathode is formed at 20 (FIG. 4).

[0029] As will be appreciated, prior art processes utilizing lithium hydroxide cannot be heated in metals due to melting of the lithium hydroxide which is corrosive to the metal and forms agglomerated powder. For purposes of the present invention, the precursor has less than 5% by weight lithium hydroxide, more preferably less than 4% by weight lithium hydroxide, even more preferably less than 1% by weight lithium hydroxide, even more preferably less than 0.1% by weight lithium hydroxide, and most preferably undetectable lithium hydroxide.

[0030] The metal salts of the multicarboxylic acids can be formed by digesting digestible metal salts such as metal carbonates or by direct reaction of the elemental metal with the multicarboxylic acid. The multicarboxylic acid contains at least two carboxyl groups. A particularly preferred multicarboxylic acid is oxalic acid, due in part to the minimization of carbon that must be removed during calcination. Other low molecular weight dicarboxylic acids such as malonic acid, succinic acid, glutaric acid and adipic acid can be used. Higher molecular weight dicarboxylic acids can be used. Particularly preferred are dicarboxylic acids with an even number of carbons due to their higher solubility, but the need to remove additional carbon and reduced solubility make them less desirable. Other acids such as citric acid, lactic acid, oxaloacetic acid, fumaric acid, maleic acid and other polycarboxylic acids can be utilized, provided they have sufficient solubility to achieve at least a small stoichiometric excess and have sufficient chelating properties. It is preferred not to use acids with hydroxyl groups as they are highly hygroscopic.

[0031] A special feature of the present invention is the formation of a pre-lithiated salt as an intermediate prior to the mineralization process. The precursor lithium salt, as a non-limiting example, lithium oxalate, forms lithium oxide directly in the presence of metals without forming a liquid phase. Thus, lithium is incorporated into the metal salt prior to calcination, improving the efficiency of lithium incorporation.

[0032] A particular advantage of the present invention is that the intermediate material is preferably formed in a metal vessel with rotation or stirring in the first vessel. In a particularly preferred method, the organic salt precursor can be heated in a rotary kiln as the first vessel using a high temperature steel tube to produce a uniform and free-flowing powder. Since the precursor can be rotated or stirred, a larger amount of material can be heated compared to conventional methods involving kilns and relatively static powders. This is possible because the One-Pot process forms lithium oxide directly from an organometallic salt such as lithium oxalate, which is preferred over the addition of LiOH in the precursor. When LiOH is used in the precursor, it generally melts at the pre-calcination temperature, causing the reactants to adhere to the inner surface of the tube. By using any kiln with heating and stirring, such as a rotary kiln, the intermediate material can be mixed while heating to produce a homogenous material. In contrast, static calcination generally gives a range of compositions from top to bottom in the sagger.

[0033] The one-pot process intimately mixes all reactants together where the lithium salt is extremely finely distributed throughout the precursor. This is an improvement over the traditional method of adding LiOH as a co-mixed fine powder. Without being limited by theory, it is hypothesized that the organic salt forms the desired lithiated crystal structure during initial heating. Based on that, the intermediate material, while not completely formed into the final active material, has already formed the correct crystal structure and therefore has Li incorporated into the oxide lattice structure. +It is assumed that the oxide lattice structure is already lithiated at 300°C. The formation of the desired crystal structure occurs as low as 200°C and is complete at 600°C. In the prior art, it is assumed that the oxide lattice structure does not form at such low temperatures because lithium cannot be significantly incorporated into the lattice and therefore the desired crystal structure cannot be formed. Thus, the material added to the sager for the final calcination / crystallization calcination and calcination time is already stoichiometric with minimal or no further loss of material which is expected to improve kiln utilization. Reducing the time at calcination temperature is particularly important when forming products in O2 such as high Ni NMC. It is easier to maintain the desired O2 partial pressure in the calcination kiln during the final high temperature calcination since CO2 or water evolution is significantly reduced and theoretically neither is reduced.

[0034] The intermediate comprises the desired crystal structure, as described elsewhere. [ka] It is particularly preferred that the space group contains at least 50% by weight of material having a crystalline structure. More preferably, the intermediate material contains at least 75% by weight of R3m or [ka] Even more preferably, the intermediate material comprises at least 90% by weight of R3m or [ka] Most preferably, the intermediate material is at least 99% by weight of R3m or [ka] Includes materials having a crystalline structure in a space group.

[0035] The surface area of ​​the intermediate material is 7m 2 / g, and preferably exceeds 9m 2 More preferably, it is greater than 10m 2 More preferably, it is greater than 45m 2 / g. Once the proper crystal lattice is achieved and the precursors are removed, further heating increases the crystallinity and decreases the surface area. Fully sintered material typically has a surface area of ​​about 2 m 2 Theoretically, however, it is possible to achieve complete sintering at lower temperatures, but the time required to achieve it is impractical. It is therefore preferable to achieve an intermediate material with high purity and high surface area for subsequent sintering in a separate step. In prior art processes, fully lithiated material crystallized with the desired space group symmetry could not be achieved with such a high surface area because the surface area is dramatically reduced during lithiation of the pre-calcined material.

[0036] Since the intermediate material is already in the proper crystal lattice, it is hypothesized that a second heating to the calcination temperature in a second vessel will increase the crystallinity with a concomitant decrease in surface area. Lithium migration into the lattice has already occurred and presumably the time required at the calcination temperature is significantly reduced compared to conventional methods. The result is the ability to load the intermediate material, which is already near stoichiometric, into a second vessel such as a sagger, optimizing sagger and kiln use and optimizing kiln utilization.

[0037] Because the intermediate material is a free-flowing powder, the types of kilns suitable for use in calcination exceed those currently considered appropriate. Thus, the kiln type may be selected based on the scale of operation. Kilns utilizing interchangeable saggers include, but are not limited to, muffle kilns, roller hearth kilns, or pusher kilns, in part, which are preferred due to their large installed base. Rotary kilns are particularly preferred for the formation of the intermediate material due to their high throughput and cost relative to the use of saggers in the kiln.

[0038] At lower temperatures, about 200-400°C, fluidized beds can achieve the same effect of oxidation and mixing. These systems are expensive and not efficient in their use of energy.

[0039] Particularly preferred active cathode materials are A spinel crystal structure defined by formula I: LiNi x Mn y Co z E w O4 Formula I where E is an optional dopant; x+y+z+w = 2 and w≦0.2; or The rock salt crystal structure defined by Formula II; LiNi a Mn b X c G d O2 Formula II wherein G is an optional dopant; X is Co or Al; a+b+c+d=1, d≦0.1.

[0040] In a preferred embodiment, the spinel crystal structure of formula I has 0.45≦x≦0.60; 1.40≦y≦1.50 and z≦0.90. More preferably, 0.45≦x≦0.55, 1.45≦y≦1.50, z≦0.05. In a preferred embodiment, neither x nor y is zero. In formula I, it is preferred that the Mn / Ni ratio is 3.00 or less, preferably at least 2.33 to less than 3, most preferably at least 2.60 to less than 3.00.

[0041] In a preferred embodiment, the rock salt crystal structure of formula II is a high nickel NMC, with 0.50≦a≦0.96, more preferably 0.50≦a≦0.94, even more preferably 0.50≦a≦0.92, even more preferably 0.58≦a≦0.62, as represented by NMC 622, or 0.78≦a≦0.82, as represented by NMC 811. In a preferred embodiment, a=b=c, as represented by NMC 111. The term NMCxxx is an abbreviation used in the art to represent the nominal relative ratios of nickel, manganese, and cobalt. NMC811, for example, represents LiNi0.8Mn0.1Co0.1O2.

[0042] In the formulas throughout this specification, lithium is defined as stoichiometrically balanced charge, with the understanding that lithium is mobile between the anode and the cathode. Thus, at any given time, the cathode may be relatively lithium rich or relatively lithium deficient. In a lithium deficient cathode, lithium is below stoichiometric balance, and upon charging, lithium may exceed stoichiometric balance. Similarly, in the formulations listed throughout this specification, the metals are expressed as charge balanced, with the understanding that the metals may be slightly rich or slightly deficient, as determined by elemental analysis, since it is not possible to formulate a completely balanced stoichiometry in practice.

[0043] Dopants can be added to improve the properties of the oxide, such as electronic conductivity and stability. The dopants are preferably substitutional dopants added in concert with the primary nickel, manganese, and any cobalt or aluminum. The dopants preferably comprise no more than 10 mol % of the oxide, preferably no more than 5 mol %. Preferred dopants include Al, Gd, Ti, Zr, Mg, Ca, Sr, Ba, Mg, Cr, Cu, Fe, Zn, V, Bi, Nb, and B, with Al and Gd being particularly preferred. Dopants and coating materials can be added as known in the art. EXAMPLES

[0044] Lithium nickel metal oxide in spinel crystal structure LNMO was prepared using precursor material containing lithium, nickel and manganese oxalates. In the inventive example, the precursor material was heated in a rotary kiln at 500°C. In the comparative example, the same precursor material was heated in a sagger at the same temperature. X-ray diffraction (XRD) patterns of the intermediate material heated to 925°C and the final calcined product showed a lithiated spinel crystal structure with no sign of impurities. In the case of the intermediate material, the peaks are broader, suggesting very small crystals. The peaks grow and become sharper after calcination. The XRD patterns of the intermediate material are shown in Figure 1. In Figure 1, the XRD pattern of the intermediate material calcined in a sagger at 500°C for 5 hours is Scan A, the XRD pattern of the intermediate material calcined in a rotary kiln at 500°C for 5 hours is Scan B, and the XRD pattern of the fully calcined LNMO product after calcination at 925°C is Scan C. As can be seen, the XRD shows that the intermediate and final calcined LNMO have the same crystal lattice.

[0045] It is clear that pure single-phase lithiated LNMO forms at about 500°C. Figure 2 shows that the same phase forms even after 1 hour at 350°C, suggesting rapid and complete lithiation at this low temperature. After the final high-temperature calcination, the peaks become much sharper as the crystals grow. In Figure 2, scans A, B, and C are XRD patterns of LNMO after pre-calcination at 350°C for 1, 3, and 5 hours, respectively, and scans D, E, and F are of LNMO after pre-calcination at 500°C for 1, 3, and 5 hours, respectively.

[0046] As will be appreciated, LNMO has a low initial surface area which decreases with subsequent sintering. A typical LNMO pre-calcined at 350°C that is fully lithiated as described above has a surface area of ​​about 38m. 2 / g, and after sintering at 925 °C for 15 h, the same sample had a surface area of ​​about 1.1 m 2 A similar representative LNMO pre-calcined at 500°C for 5 hours has a surface area of ​​about 14 m 2 / g, and after sintering at 925 °C for 15 h, the same sample had a surface area of ​​about 0.8 m 2 / g surface area.

[0047] Nominally LiNi 0.8 Mn 0.1 Co 0.1 The formation of NMC 811 with O2 was compared as well as final calcination in oxygen. In Figure 3, the XRD patterns of the powder precursor, pre-calcined intermediate material, and final NMC 811 are provided in scans a, b, and c, respectively. The pre-calcined material shows some of the major NMC peaks formed along with traces of Li2CO3 peaks as an impurity. This suggests that lithiation is initiated even at high nickel contents. The pre-calcined intermediate material has a lithiation rate of about 23–26 mN. 2 The final high-temperature firing has a surface area of ​​about 0.3 to 0.5 m 2 The resulting mixture is pure single-phase NMC 811 with a surface area of ​​1 / g.

[0048] The precursor can be pre-calcined in a rotary kiln with a hot steel tube to produce a uniform, free-flowing intermediate powder. This advantage is provided by a one-pot process in which a Li feedstock, such as Li2CO3 or LiOH, is converted to lithium oxalate before the initial calcination to form the intermediate material, which differs from conventional methods that present LiOH for calcination. Lithium oxalate decomposes to lithium oxide or carbonate at low temperatures, but LiOH generally melts at the pre-calcination temperature, depositing all onto the inner surface of the tube.

[0049] The present invention offers significant advantages as it allows for the use of rotary kilns or stirred processes where lithium oxalate can be calcined instead of lithium carbonate or lithium hydroxide and the kiln surfaces in contact with the material being heated can be metallic instead of ceramic, providing significant advantages in terms of efficiency and cost.

[0050] While the present invention has been described with reference to preferred embodiments, it is not limited thereto. Those skilled in the art will recognize additional embodiments that are contemplated and set forth in the claims appended hereto.

Claims

1. forming a precursor comprising a lithium salt and at least one multicarboxylate of nickel, manganese or cobalt; heating the precursor to a temperature of 600° C. or less in a metal lined vessel to form an intermediate material; heating the intermediate material to a temperature greater than 600° C. to form an active cathode material; A method of forming an active cathode material, wherein the precursor contains less than 5% by weight lithium hydroxide or no lithium hydroxide.

2. 2. The method of forming an active cathode material of claim 1, wherein the lithium salt is a lithium carboxylate or a lithium multicarboxylate, or the lithium salt is lithium acetate or lithium oxalate.

3. 10. The method of forming an active cathode material according to claim 1, wherein the precursor comprises at least one salt selected from the group consisting of nickel oxalate, manganese oxalate, and cobalt oxalate.

4. 2. The method of claim 1, wherein the metal lined vessel is a rotary kiln, or a rotary kiln containing a nickel alloy, or a metal lined kiln, or a metal lined kiln that is a rotary kiln, or a metal lined kiln that is a rotary kiln containing a nickel alloy.

5. 2. The method of claim 1 , wherein the active cathode material is selected from the group consisting of: LiNi x Mn y Co z E w O 4 Formula I where E is an optional dopant, and x+y+z+w=2, w≦0.2; and LiNi a Mn b X c G d O 2 Formula II where G is an optional dopant. X is Co or Al, and a+b+c+d=1, and d≦0.

1.

6. 6. The method of forming an active cathode material of claim 5, wherein in Formula I, 0.45≦x≦0.60, 1.40≦y≦1.50, and z≦0.90; or 0.45≦x≦0.55, 1.45≦y≦1.50, and z≦0.

05.

7. 6. The method of forming an active cathode material of claim 5, wherein in formula I, neither x nor y is zero.

8. 6. The method of forming an active cathode material according to claim 5, wherein in formula I, the Mn / Ni ratio is less than or equal to 3.00, or the Mn / Ni ratio is at least 2.33 and less than 3.00, or the Mn / Ni ratio is at least 2.60 and less than 3.

00.

9. 6. The method for forming an active cathode material according to claim 5, wherein in Formula II, 0.50≦a≦0.96, or 0.50≦a≦0.94, or 0.58≦a≦0.62, or 0.78≦a≦0.

82.

10. 6. The method of forming an active cathode material of claim 5, wherein E or G is selected from the group consisting of Al, Gd, Ti, Zr, Mg, Ca, Sr, Ba, Mg, Cr, Cu, Fe, Zn, V, Bi, Nb, and B, or wherein E or G is selected from the group consisting of Al and Gd.

11. 10. The method of forming an active cathode material as defined in claim 1, further comprising the step of transferring said intermediate material to a second container after said heating to below 600°C.

12. At least 50% by weight, or 95% by weight, or 99% by weight of said intermediate material 【Chemistry 1】 has a crystal structure in a space group, or 【Chemistry 2】 10. The method of forming the active cathode material of claim 1 having a crystal structure in a space group:

13. The intermediate material is 7 m 2 / g or more than 9 m 2 / g or more than 10 m 2 / g or more than 45 m 2 2. The method of forming the active cathode material of claim 1 having a surface area not exceeding 100 / g.

14. 10. The method of claim 1, wherein the step of heating the intermediate material is at a temperature of at least 700°C and up to 925°C.

15. 10. The method of forming an active cathode material as recited in claim 1, wherein the intermediate material has less than 0.4% by weight carbon.

16. 10. The method of forming an active cathode material as claimed in claim 1, wherein said heating of said precursor is carried out in an atmosphere comprising oxygen.

17. 10. The method of claim 1 further comprising forming the precursor by reaction of at least one carbonate of nickel, manganese, or cobalt with a dicarboxylic acid, or further comprising forming the precursor by reaction of at least one carbonate of nickel, manganese, or cobalt with oxalic acid, or further comprising forming the precursor by reaction of at least one of elemental nickel, manganese, or cobalt with a dicarboxylic acid, or further comprising forming the precursor by reaction of at least one of elemental nickel, elemental manganese, or cobalt with oxalic acid.

18. forming a precursor comprising a lithium salt and at least one multicarboxylate of nickel, manganese or cobalt; heating the precursor to a temperature of 600° C. or less in a first vessel having a metal lining to form an intermediate material; transferring the intermediate material to a second container; heating the intermediate material in the second container to a temperature greater than 600° C. to form an active cathode material; A method of forming an active cathode material, wherein the precursor contains less than 5% by weight lithium hydroxide or no lithium hydroxide.

19. The method of forming an active cathode material as described in claim 18, wherein the first vessel is a rotary kiln, or is a metal lined kiln, or is a metal lined kiln wherein the metal is a nickel alloy.

20. 20. The method of forming an active cathode material as claimed in claim 18, wherein the lithium salt is a lithium carboxylate or lithium multicarboxylate, or the lithium salt is lithium carbonate or lithium oxalate.

21. 20. The method of forming an active cathode material according to claim 18, wherein the precursor comprises at least one salt selected from the group consisting of nickel oxalate, manganese oxalate, and cobalt oxalate.

22. The active cathode material is LiNi x Mn y Co z E w O 4 Formula I where E is an optional dopant; and x+y+z+w=2, w≦0.2; and LiNi a Mn b X c G d O 2 Formula II where G is an optional dopant; X is Co or Al; Wherein a+b+c+d=1 and d≦0.1; 20. The method of forming an active cathode material of claim 18, wherein the active cathode material is selected from the group consisting of:

23. 23. The method of forming an active cathode material of claim 22, wherein in Formula I, 0.45≦x≦0.60, 1.40≦y≦1.50, and z≦0.90; or 0.45≦x≦0.55, 1.45≦y≦1.50, and z≦0.

05.

24. 23. The method of forming an active cathode material according to claim 22, wherein in formula I, neither x nor y is zero.

25. 23. The method of forming an active cathode material according to claim 22, wherein in Formula I, the Mn / Ni ratio is less than or equal to 3.00, or the Mn / Ni ratio is at least 2.33 and less than 3.00, or the Mn / Ni ratio is at least 2.60 and less than 3.

00.

26. 23. The method of forming an active cathode material according to claim 22, wherein in Formula II, 0.50≦a≦0.96, or 0.50≦a≦0.94, or 0.58≦a≦0.62, or 0.78≦a≦0.

82.

27. 23. The method of forming an active cathode material of claim 22, wherein E or G is selected from the group consisting of Al, Gd, Ti, Zr, Mg, Ca, Sr, Ba, Mg, Cr, Cu, Fe, Zn, V, Bi, Nb, and B, or wherein E or G is selected from the group consisting of Al and Gd.

28. 20. The method of forming an active cathode material as defined in claim 18, further comprising the step of: transferring the intermediate material to a second container after said heating to below 600°C.

29. at least 50% by weight, or 95% by weight, or 99% by weight of said intermediate material has a crystal structure in the R3m space group; or 【Chemistry 3】 20. The method of forming an active cathode material as recited in claim 18, having a crystal structure in a space group:

30. The intermediate material is 7 m 2 / g or more than 9 m 2 / g or more than 10 m 2 / g, or the intermediate material has a surface area of ​​more than 45 m 2 20. The method of forming an active cathode material as claimed in claim 18, having a surface area not exceeding 100 / g.

31. 20. The method of forming an active cathode material as set forth in claim 18, wherein the step of heating the intermediate material is at a temperature of at least 700° C. and not more than 925° C.

32. 20. The method of forming an active cathode material as claimed in claim 18, wherein the intermediate material has less than 0.4% by weight carbon.

33. 20. The method of forming an active cathode material as claimed in claim 18, wherein said heating of said precursor is carried out in an atmosphere comprising oxygen.

34. 20. The method of forming an active cathode material as claimed in claim 18, further comprising forming the precursor by reaction of at least one of elemental nickel, elemental manganese, or elemental cobalt with a dicarboxylic acid.

35. 20. The method of forming an active cathode material as claimed in claim 18, wherein the multi-carboxylic acid is oxalic acid.

36. A method for producing a precursor comprising: forming a precursor comprising a lithium multicarboxylate and at least one multicarboxylate of nickel, manganese, or cobalt; heating the precursor to a temperature of 600° C. or less in a metal-lined rotary kiln vessel to form an intermediate material; and heating the intermediate material to a temperature greater than 600° C. to form an active cathode material; A method of forming an active cathode material, wherein the precursor contains less than 5% by weight lithium hydroxide or no lithium hydroxide.

37. The method of forming an active cathode material as described in claim 36, wherein the multi-carboxylate lithium salt is lithium oxalate.

38. 37. The method of forming an active cathode material according to claim 36, wherein the precursor comprises at least one salt selected from the group consisting of nickel oxalate, manganese oxalate, and cobalt oxalate.

39. A method for forming an active cathode material as described in claim 36, wherein the rotary kiln vessel is a metal lined vessel, or a metal lined vessel comprising a nickel alloy, or a metal lined kiln, or a metal lined kiln comprising a nickel alloy.

40. The active cathode material is LiNi x Mn y Co z E w O 4 Formula I where E is an optional dopant; and x+y+z+w=2, w≦0.2, and LiNi a Mn b X c G d O 2 Formula II where G is an optional dopant; X is Co or Al; and Wherein a+b+c+d=1 and d≦0.1; 37. The method of forming an active cathode material of claim 36, wherein the active cathode material is selected from the group consisting of:

41. 41. The method of forming an active cathode material of claim 40, wherein, in Formula I, 0.45≦x≦0.60, 1.40≦y≦1.50, and z≦0.90; or 0.45≦x≦0.55, 1.45≦y≦1.50, and z≦0.

05.

42. 41. The method of forming an active cathode material according to claim 40, wherein in formula I, neither x nor y is zero.

43. 41. The method of forming an active cathode material as claimed in claim 40, wherein in Formula I, the Mn / Ni ratio is less than or equal to 3.00, or the Mn / Ni ratio is at least 2.33 and less than 3.00, or the Mn / Ni ratio is at least 2.60 and less than 3.

00.

44. 41. The method of forming an active cathode material of claim 40, wherein, in Formula II, 0.50≦a≦0.96, or 0.50≦a≦0.94, or 0.58≦a≦0.62, or 0.78≦a≦0.

82.

45. 41. The method of forming an active cathode material of claim 40, wherein E or G is selected from the group consisting of Al, Gd, Ti, Zr, Mg, Ca, Sr, Ba, Mg, Cr, Cu, Fe, Zn, V, Bi, Nb and B, or wherein E or G is selected from the group consisting of Al and Gd.

46. 37. The method of forming an active cathode material as set forth in claim 36, further comprising transferring the intermediate material to a second container after said heating to below 600°C.

47. At least 50% by weight, or 95% by weight, or 99% by weight of the intermediate material 【Chemistry 4】 has a crystal structure in a space group, or 【Chemistry 5】 37. The method of forming an active cathode material as recited in claim 36, having a crystal structure in a space group:

48. The intermediate material is 7 m 2 / g or 9m 2 / g or more than 10 m 2 / g or more than 45 m 2 37. The method of forming an active cathode material as claimed in claim 36, wherein the active cathode material has a surface area not exceeding 100 / g.

49. 37. The method of forming an active cathode material as set forth in claim 36, wherein the step of heating the intermediate material is at a temperature of at least 700°C and up to 925°C.

50. 37. The method of forming an active cathode material as claimed in claim 36, wherein the intermediate material has less than 0.4% by weight carbon.

51. 37. The method of forming an active cathode material as claimed in claim 36, wherein said heating of said precursor is carried out in an atmosphere comprising oxygen.

52. 37. The method of forming an active cathode material of claim 36, further comprising forming the precursor by reaction of at least one carbonate of nickel, manganese, or cobalt with a dicarboxylic acid, or further comprising forming the precursor by reaction of at least one carbonate of nickel, manganese, or cobalt with oxalic acid, or further comprising forming the precursor by reaction of at least one of elemental nickel, elemental manganese, or elemental cobalt with a dicarboxylic acid, or further comprising forming the precursor by reaction of at least one of elemental nickel, elemental manganese, or elemental cobalt with oxalic acid.